2013
DOI: 10.5489/cuaj.1074
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of prostate cancer local recurrence by urinary prostate-specific antigen

Abstract: Purpose: We assessed the role of urinary prostate-specific antigen (uPSA) in the follow-up of prostate cancer after retropubic radical prostatectomy (RRP) for the early detection of local recurrences. Methods:We recruited 50 patients previously treated for prostate cancer with RRP and who had not experienced a prostatespecific antigen (PSA) recurrence within their first postoperative year into a cross-sectional laboratory assessment and prospective 6-year longitudinal follow-up study. We defined biochemical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…8,17 In this case, further expensive surgical procedures such as biopsies often have to be used for the detection of early prostate cancer. Recently, Bolduc et al 37,38 evaluated the usefulness of urinary PSA in the differential diagnosis of prostate cancer and BPH, and found that the level of urinary PSA was 52.6 ng mL À1 for prostate cancer patients and 123.2 ng mL À1 for the patients with BPH, respectively. By comparing this with the concentration (about 105 ng mL À1 ) of normal urinary PSA, which is much higher than that of normal serum PSA because PSA in prostatic fluid readily comes into urine, 39 they proposed that lower urinary PSA points toward prostate cancer, and urinary PSA may serve as a useful marker in the differential diagnosis of prostate cancer and BPH, especially when serum PSA is between 2.5 ng mL À1 and 10 ng mL À1 .…”
Section: Detection Of Proteolytically Active Psa In Urinementioning
confidence: 99%
“…8,17 In this case, further expensive surgical procedures such as biopsies often have to be used for the detection of early prostate cancer. Recently, Bolduc et al 37,38 evaluated the usefulness of urinary PSA in the differential diagnosis of prostate cancer and BPH, and found that the level of urinary PSA was 52.6 ng mL À1 for prostate cancer patients and 123.2 ng mL À1 for the patients with BPH, respectively. By comparing this with the concentration (about 105 ng mL À1 ) of normal urinary PSA, which is much higher than that of normal serum PSA because PSA in prostatic fluid readily comes into urine, 39 they proposed that lower urinary PSA points toward prostate cancer, and urinary PSA may serve as a useful marker in the differential diagnosis of prostate cancer and BPH, especially when serum PSA is between 2.5 ng mL À1 and 10 ng mL À1 .…”
Section: Detection Of Proteolytically Active Psa In Urinementioning
confidence: 99%
“…Urine is nowadays being considered as an alternative biological fluid to serum in the search for new PCa markers . Thus, we have used purified PSA from 2 mL of urine obtained after digital rectal examination, with a high content of PSA.…”
Section: Resultsmentioning
confidence: 99%
“…n Urinary PSA The measurement of PSA in urine has dated back to 1985 [17] and has since been studied as a potential biomarker for CaP. Studies have shown the clinical utility of urinary PSA by itself or in conjunction with serum PSA for diagnosing CaP and predicting disease recurrence [18][19][20][21]. The clinical utility of the urine:serum PSA ratio was demonstrated in a prospective multicenter study that showed that urine PSA alone did not distinguish CaP and BPH, but when evaluated as a ratio with serum PSA, it did demonstrate significant differences, with receiver operating characteristic area under the curves (AUC) improving from 0.55 for total PSA and 0.60 for the fPSA:PSA ratio to 0.63 for the urine:serum PSA ratio [19].…”
Section: Emerging Markers and Panelsmentioning
confidence: 99%